Expression of colonic antigens by goblet and columnar epithelial cells in ileal pouch mucosa: their association with inflammatory change and faecal stasis. Issue 9 (September 1994) - Campbell, A P; Merrett, M N; Kettlewell, M; Mortensen, N J; Jewell, D P
Abstract : AIMS--To investigate colonic metaplasia of goblet and columnar epithelial cells in ileal pouch mucosa; to correlate this with the degree of morphological and inflammatory change; and to assess whether such changes are related to the presence of faecal stasis. METHODS--Biopsy specimens of ileal pouch mucosa were taken from 31 patients (30 with ulcerative colitis, one with familial adenomatous polyposis) either before (eight patients) or after (23 patients) ileostomy closure. A simple morphological technique was used to assess changes in villous height. Inflammatory change was estimated using an established scoring system for pouchitis, and acquisition of colonic antigens was determined by immunohistochemistry using three monoclonal antibodies which recognise components of the two major epithelial cell types in the colorectum. The degree of staining with the monoclonal antibodies was graded and the grades correlated with an index of villous atrophy and with the inflammatory scores. RESULTS--Five of eight (63%) pre-closure and 15 of 23 (65%) post-closure biopsy specimens showed increased staining with an antibody against components of columnar epithelial cells. One of eight (12%) pre-closure and 15 of 23 (65%) post-closure biopsy specimens stained with an antibody for colonic mucin. Although both types of staining showed a positive correlation with the pouchitis score, they also occurred in the absence of inflammation. CONCLUSIONS--Both goblet and columnar cells acquire colonic characteristics which are incomplete, but may represent a true adaptive response as they can develop in the absence of inflammation. As the change in goblet cells occurs after ileostomy closure, faecal stasis is likely to be a major contributory factor. Changes in columnar cells may occur before ileostomy closure in the absence of faecal stasis.